2010
DOI: 10.1186/1471-2229-10-42
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manganese-excess on CO2 assimilation, ribulose-1,5-bisphosphate carboxylase/oxygenase, carbohydrates and photosynthetic electron transport of leaves, and antioxidant systems of leaves and roots in Citrus grandisseedlings

Abstract: BackgroundVery little is known about the effects of manganese (Mn)-excess on citrus photosynthesis and antioxidant systems. Seedlings of sour pummelo (Citrus grandis) were irrigated for 17 weeks with nutrient solution containing 2 μM (control) or 500 μM (excess) MnSO4. The objective of this study were to understand the mechanisms by which Mn-excess leads to a decrease in CO2 assimilation and to test the hypothesis that Mn-induced changes in antioxidant systems differ between roots and leaves.ResultsMn-excess d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
65
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 73 publications
16
65
1
Order By: Relevance
“…The interference mechanisms of Al in the relations of energy absorption and electron transfer in PSII are not very clear. When in high concentrations, metals may cause a range of significantly different effects (Ralph and Burchett, 1998) like changes in both electron transfer and enzyme activities (Li et al 2010). Barazzouk et al (2005), based on electrochemical studies, attributed the effect of photoinducted electron transfer of excited chlorophyll to nanoparticles of gold.…”
Section: Resultsmentioning
confidence: 99%
“…The interference mechanisms of Al in the relations of energy absorption and electron transfer in PSII are not very clear. When in high concentrations, metals may cause a range of significantly different effects (Ralph and Burchett, 1998) like changes in both electron transfer and enzyme activities (Li et al 2010). Barazzouk et al (2005), based on electrochemical studies, attributed the effect of photoinducted electron transfer of excited chlorophyll to nanoparticles of gold.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is one of the major scavengers of hydrogen peroxide produced by cells under heavy metal stress. Because of Mn and Ni stress, significant deductibility of POD activity was reported in V. vinifera (Mn), Pistia stratiotes (Ni), Citrus grandis (Mn), O. sativa (Mn), Zea mays (Ni) (Baccouch et al, 1998;Li et al, 2010;Mou et al, 2011;Singh & Pandey, 2011;Srivastava & Dubey, 2011). As seen from Figure 4, the increasing exposure time to both metals at different concentrations showed that the enzyme activity was more reduced at the dose of 16 mg/L than the other exposure doses in both heavy metals.…”
Section: Pod Activitymentioning
confidence: 99%
“…In roots, most of the antioxidant enzymes but MDAR and DHAR remained unaffected resulting in a decrease in reduced ascorbate pools (Li et al 2010 ) . Interestingly, no effect on MDA accumulation neither in leaves nor in roots was observed, probably because the induction of antioxidant enzymes is enough to cope with increased ROS.…”
Section: Manganesementioning
confidence: 97%
“…In a recent publication, pummelo plants were grown under excessive Mn concentrations resulting in a severe impairment of the whole photosynthetic system from the donor side (PSII) to the reduction end of acceptor decrease, resulting in a reduction in the rate of CO 2 assimilation. On the contrary, the antioxidant system was enough to cope with overproduced ROS preventing further oxidative damage (Li et al 2010 ) . Changes in leaf and chloroplast ultrastructure linked to a decrease in electron transport rate and photochemical yield in response to different Mn levels have been reported in Citrus volkameriana (Papadakis et al 2007a, b ) .…”
Section: Oxidative Damage In Citrus Under Stressmentioning
confidence: 99%
See 1 more Smart Citation